Detection of subtelomere imbalance using MLPA: validation, development of an analysis protocol, and application in a diagnostic centre - Hills Alison; Madula Rajiv; Thomas Helen; Welch Alysia; Mackie Ogilvie Caroline; Ahn Joo Wook; Donaghue Celia; Mann Kathy (BMC, 2007)
Abstract Background Commercial MLPA kits (MRC-Holland) are available for detecting imbalance at the subtelomere regions of chromosomes; each kit consists of one probe for each subtelomere. Methods For validation of the kits, 208 patients were tested, of which 128 were known to be abnormal, corresponding to 8528 genomic regions overall. Validation samples included those with trisomy 13, 18 and 21, microscopically visible terminal deletions and duplications, sex chromosome abnormalities and submicroscopic abnormalities identified by multiprobe FISH. A robust and sensitive analysis system was developed to allow accurate interpretation of single probe results, which is essential as breakpoints may occur between MLPA probes. Results The validation results showed that MLPA is a highly efficient technique for medium-throughput screening for subtelomere imbalance, with 95% confidence intervals for positive and negative predictive accuracies of 0.951-0.996 and 0.9996-1 respectively. A diagnostic testing strategy was established for subtelomere MLPA and any subsequent follow-up tests that may be required. The efficacy of this approach was demonstrated during 15 months of diagnostic testing when 455 patients were tested and 27 (5.9%) abnormal cases were detected. Conclusion The development of a robust, medium-throughput analysis system for the interpretation of results from subtelomere assays will be of benefit to other Centres wishing to implement such an MLPA-based service.